Composite graphite material as well as preparation method and application thereof

By using resin and modified asphalt as coating agents in the preparation process of composite graphite materials, the problem of insufficient composite uniformity is solved, and the circulation performance of the battery is significantly improved.

CN119673998APending Publication Date: 2025-03-21FUJIAN SHANSHAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411812952.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing composite graphite materials have defects in composite uniformity, resulting in poor cycling performance of the battery.

Method used

The uniformity and performance optimization of the composite material are ensured by mixing natural graphite with the first coating agent, followed by artificial graphite and second coating agent (modified asphalt), and carbonization.

Benefits of technology

High composite uniformity of composite graphite materials is achieved, and the electrochemical performance of the battery is significantly improved, especially the cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a composite graphite material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, mixing natural graphite and a first coating agent to obtain a mixture A; s2, mixing the mixture A, artificial graphite and a second coating agent to obtain a mixture B, and carbonizing; wherein the first coating agent comprises resin; the second coating agent comprises modified asphalt. The obtained composite graphite material has excellent performances of natural graphite and artificial graphite, also has relatively high composite uniformity, and can obviously improve the electrochemical performance of a battery after being used for the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite graphite material and a preparation method and application thereof. Background Art

[0002] In modern battery technology, graphite materials have become the first choice for negative electrode materials of lithium-ion batteries due to their excellent conductivity, chemical stability and relatively low cost. Natural graphite and artificial graphite are the two main graphite materials. Natural graphite is widely used for its high conductivity and high crystallinity, but it usually has unevenness and low cycle times. Artificial graphite has higher consistency and excellent mechanical properties, but its conductivity and cost-effectiveness may not be as good as natural graphite. Therefore, it is necessary to manufacture a negative electrode material that combines the two to combine the high conductivity of natural graphite and the high consistency of artificial graphite, thereby improving the overall performance of the battery.

[0003] For example, patent application CN117800335A discloses a process for preparing a composite material of artificial graphite and carbon-coated natural graphite, which specifically includes: modifying artificial graphite with electromagnetic microwaves under an inert gas protection state to obtain modified artificial graphite; blending spherical natural graphite and the coating material uniformly, and then carbonizing them in an inert atmosphere to obtain modified natural graphite; blending the modified artificial graphite and the modified natural graphite uniformly to obtain a composite material. However, this composite method still has the defect of poor composite uniformity, which leads to poor cycle performance of the resulting battery.

[0004] Therefore, there is an urgent need for a composite graphite material that can effectively improve the composite uniformity of natural graphite and artificial graphite. Summary of the invention

[0005] In order to overcome the above technical defects of existing composite graphite materials, the present invention proposes a composite graphite material and its preparation method and application. The obtained composite graphite material has the excellent properties of both natural graphite and artificial graphite, and also has high composite uniformity. After being used in batteries, its electrochemical performance, especially cycle performance, can be significantly improved.

[0006] To achieve the above purpose, the present invention adopts the following technical solution.

[0007] The present invention provides a method for preparing a composite graphite material, which comprises the following steps:

[0008] S1, mixing natural graphite and a first coating agent to obtain a mixture A;

[0009] S2, mixing the mixture A, artificial graphite and a second coating agent to obtain a mixture B, and carbonizing the mixture;

[0010] Wherein, the first coating agent comprises resin;

[0011] The second coating agent includes modified asphalt.

[0012] In the present invention, in step S1, the natural graphite may refer to graphite naturally formed in nature, or natural graphite obtained by conventional physical operations such as crushing and classification; that is, the graphite itself does not involve any chemical changes in the whole process, and those skilled in the art may know its specific meaning.

[0013] In some embodiments, in step S1, the natural graphite is spherical, and the particle size D50 of the natural graphite is preferably 4-8 μm.

[0014] In some embodiments, in step S1, the carbon content of the natural graphite is not less than 90 wt%.

[0015] In the present invention, in step S1, the resin may refer to a natural resin formed in nature, or a synthetic resin obtained by a conventional synthetic reaction; the natural resin may include, for example, one or more of amber, rosin, lacquer and dammar resin; the synthetic resin may include, for example, one or more of phenolic resin, polyester resin and polyamide resin. Those skilled in the art may know the specific meaning thereof.

[0016] In some embodiments, in step S1, the resin is a phenolic resin.

[0017] In the present invention, in step S1, the resin may refer to a resin containing impurities, and the impurities may be impurities generated during resin collection, resin raw materials and resin production, for example, including one or more of grease, moisture, oxides, metal ions and resin monomers. Those skilled in the art may know the specific meaning.

[0018] In some embodiments, in step S1, the purity of the resin is 65wt%-75wt%, preferably 70wt%-75wt%. The purity refers to the mass percentage of the resin excluding impurities in the total mass of the resin.

[0019] In some embodiments, in step S1, the viscosity of the resin at 25°C is 300-800 cp, preferably 400-800 cp.

[0020] In some embodiments, in step S1, the gelation time of the resin at 25° C. is 80-130 s, preferably 80-120 s. The gelation time refers to the time it takes for a resin material to change from a liquid state to a gel state under specific conditions (such as 25° C.).

[0021] In some embodiments, in step S1, the mass ratio of the natural graphite to the first coating agent is 80:20-95:5, preferably 90:10.

[0022] In some embodiments, in step S1, the mixing time is 0.5-2 h, for example, 1 h.

[0023] In some embodiments, in step S1, the mixing is performed by a horizontal-shaft ribbon mixer.

[0024] In some preferred embodiments, in step S1, after the mixing step, a pre-carbonization step is further included; the pre-carbonization includes a heating stage and a heat preservation stage.

[0025] Wherein, the heating rate in the heating stage is preferably 5-15°C / min.

[0026] The temperature in the insulation stage is preferably 300-400°C, for example 350°C.

[0027] The duration of the insulation stage is preferably 6-10 hours, for example 8 hours.

[0028] Wherein, the pre-carbonization is preferably carried out in a roller kiln.

[0029] Wherein, the pre-carbonization is preferably carried out in an inert atmosphere.

[0030] The inert atmosphere is preferably nitrogen or argon.

[0031] The gas flow rate of the inert atmosphere is preferably 2 L / h-20 L / h, such as 10 L / h.

[0032] In the present invention, in step S2, the artificial graphite may refer to a graphite material obtained by high-temperature treatment of organic carbonization and graphitization, which can generally be obtained by carbonizing and graphitizing a carbonaceous raw material and a binder, and those skilled in the art will know its specific meaning.

[0033] In some embodiments, in step S2, the particle size D50 of the artificial graphite is 8-12 μm.

[0034] In some embodiments, in step S2, the specific surface area of ​​the artificial graphite is 1-1.6 m 2 / g.

[0035] In some embodiments, in step S2, the discharge capacity of the artificial graphite is 352-355 mAh / g.

[0036] In some embodiments, in step S2, the method for preparing artificial graphite comprises the following steps:

[0037] The steps of carbon raw materials crushing, shaping, mixing with binder, granulation and graphitization.

[0038] Wherein, the carbonaceous raw material is preferably petroleum coke.

[0039] Wherein, the comminution is preferably performed by a jaw crusher.

[0040] Wherein, the shaping is preferably performed by grading.

[0041] The particle size D50 of the product after shaping is preferably 6-8 μm.

[0042] Wherein, the binder is preferably asphalt, such as base asphalt.

[0043] The amount of the adhesive used is preferably 15-20% of the mass of the shaped product, for example 18%.

[0044] Wherein, the graphitization temperature is preferably 2800-3000°C.

[0045] In the present invention, in step S2, the modified asphalt may refer to an asphalt compound in which a conventional modifier is added to the base asphalt or the base asphalt is lightly oxidized to improve the performance of the base asphalt; the base asphalt may be one or more of natural asphalt, coal tar asphalt and petroleum asphalt; the modified asphalt may include one or more of polymer modified asphalt, elastomer modified asphalt, waterproofing agent modified asphalt and additive modified asphalt, for example, one or more of SBS modified asphalt, SBR modified asphalt and EVA modified asphalt. Those skilled in the art may know its specific meaning.

[0046] In some embodiments, in step S2, the modified asphalt is SBS modified asphalt.

[0047] In some embodiments, in step S2, the particle size D50 of the modified asphalt is 2-6 μm, preferably 2.5-4.5 μm.

[0048] In some embodiments, in step S2, the coking value of the modified asphalt is not higher than 30%, preferably 15-25%.

[0049] In some embodiments, in step S2, the density of the modified asphalt at 30°C is 1-1.1 g / cm 3 .

[0050] In some embodiments, in step S2, the mass ratio of the artificial graphite to the second coating agent is 80:20-90:10, preferably 85:15.

[0051] In some embodiments, the mass ratio of the natural graphite in step S1 to the artificial graphite in step S2 is 1:1-1:2.

[0052] In some embodiments, in step S2, the carbonization includes a temperature rising stage and a temperature keeping stage.

[0053] Wherein, the heating rate in the heating stage is preferably 10-15°C / min.

[0054] Wherein, the temperature in the insulation stage is preferably 1000-1200°C.

[0055] The duration of the insulation stage is preferably 22-26 hours, such as 24 hours.

[0056] In some preferred embodiments, the heating rate of the pre-carbonization heating stage in step S1 is lower than the heating rate of the carbonization heating stage in step S2.

[0057] In some embodiments, in step S2, the carbonization is performed in a roller kiln.

[0058] In some embodiments, in step S2, the carbonization is performed in an inert atmosphere.

[0059] Wherein, the inert atmosphere is preferably nitrogen or argon.

[0060] The gas flow rate of the inert atmosphere is preferably 2 L / h-20 L / h, for example 10 L / h.

[0061] In some embodiments, in step S2, the carbonization further includes the steps of shaping, grading, screening and demagnetization.

[0062] The present invention also provides a composite graphite material, which is prepared by the method for preparing the composite graphite material as described above.

[0063] In some embodiments, the particle size D50 of the composite graphite material is 12-14 μm.

[0064] In some embodiments, the composite graphite material has a tap density of 0.9-1.4 g / cm³.

[0065] In some embodiments, the powder pressure of the composite graphite material is 1.9-2.3 g / cm³.

[0066] In some embodiments, the specific surface area of ​​the composite graphite material is 0.65-2.5 m 2 / g.

[0067] The present invention also provides an application of the composite graphite material as mentioned above in the field of electrochemistry.

[0068] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0069] The reagents and raw materials used in the present invention are commercially available.

[0070] The positive and progressive effects of the present invention are:

[0071] The composite graphite material of the present invention uses a specific coating method to composite natural graphite and artificial graphite, combining the advantages of natural graphite and artificial graphite while ensuring high composite uniformity; the obtained composite graphite material can significantly improve the discharge capacity and cycle performance of the battery after being used in the battery. The method is simple to operate as a whole, easy to implement, and has obvious effects, and can be used for industrial production. DETAILED DESCRIPTION

[0072] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0073] In the following examples and comparative examples, the raw material information used is as follows:

[0074] Resin: viscosity is 300-800cp (25℃), gel time is 80-130s (25℃), purity is 70-75wt%, specific type is phenolic resin, provided by Jinan Shengquan Company;

[0075] Modified asphalt: D50=3.50±1.00μm, coking value is 15-25%, density at 30℃ is 1.05±0.05g / cm 3 , the specific type is SBS modified asphalt, provided by China Petroleum Road Star New Materials Co., Ltd.;

[0076] Petroleum coke: moisture content less than 10%, volatile matter content less than 8%, commonly available in the market;

[0077] Natural graphite raw material: specific surface area is 0.8-1.2m 2 / g, tap density is 0.75-1.00g / cm³, provided by Qingdao Xingyuan Graphite Emulsion Co., Ltd.;

[0078] Matrix asphalt: D50=3.50±1.00μm, coking value is 50-70%, provided by Jiangsu Baoli International Investment Co., Ltd.

[0079] Unless otherwise specified, the usage ratios of the raw materials in the following examples and comparative examples are all by mass ratios.

[0080] Example 1

[0081] A composite graphite material, the preparation steps of which are as follows:

[0082] 1. Preparation of artificial graphite

[0083] (1) Grinding treatment: The petroleum coke is crushed by a jaw crusher and then pulverized by a mechanical mill to obtain powder A;

[0084] (2) Shaping: Powder A is classified once according to the particle size and then shaped twice to obtain powder B. The particle size requirement is D50 = 6-8μm, and the qualified particle size ratio is > 99%;

[0085] (3) Granulation: Powder B and base asphalt are mixed evenly and granulated in a reactor to obtain powder C, where the base asphalt ratio is 18%;

[0086] (4) Graphitization: Graphitize powder C at 3000°C to obtain artificial graphite.

[0087] 2. Preparation of natural graphite

[0088] The natural graphite raw material is crushed to a particle size D50 of 4-8 μm, and classified twice to remove unqualified fine powder to obtain natural graphite.

[0089] 3. Preparation of composite graphite materials

[0090] (1) Pre-coating of natural graphite: Use a horizontal shaft ribbon mixer to mix natural graphite and resin in a ratio of 9:1 for 1 hour.

[0091] (2) High-temperature carbonization: The mixture in (1) is added to a carbonization container (roller kiln) (the entire reaction is carried out in nitrogen with a gas flow rate of 10 L / h), and the carbonization temperature is raised to 350°C at a heating rate of 5°C / min and kept at this temperature for 8 hours. According to the mass ratio of natural graphite to artificial graphite of 1:1, artificial graphite semi-finished products and modified asphalt (the ratio of artificial graphite to modified asphalt is 85%:15%) are added, and the carbonization temperature is raised to 1200°C at a heating rate of 10°C / min and kept at this temperature for 24 hours to obtain a carbonized product.

[0092] (3) Shaping and grading: The carbonized product is shaped and graded, with the requirement of particle size D50 = 12-14 μm.

[0093] (4) Finished product processing: The carbonized material with qualified particle size is screened twice and demagnetized twice, and the finished product is the composite graphite material of this embodiment.

[0094] Example 2

[0095] Referring to the conditions of Example 1, only step (2) in step 3 (preparation step of composite graphite material) is changed as follows:

[0096] The mixture (1) is added into a carbonization container (roller kiln) (the whole reaction is carried out in nitrogen with a gas flow rate of 10 L / h), the mass ratio of natural graphite to artificial graphite is 1:1, and then the semi-finished artificial graphite and modified asphalt (the ratio of artificial graphite to modified asphalt is 85%:15%) are added, and the carbonization temperature is increased to 1200°C at a heating rate of 10°C / min, and the temperature is kept for 24 hours to obtain a carbonized product. The carbonization container is a roller kiln, and the whole reaction is carried out in nitrogen with a gas flow rate of 10 L / h.

[0097] Example 3

[0098] Referring to the conditions of Example 1, only step (2) in step 3 (preparation step of composite graphite material) is changed as follows:

[0099] The mixture in (1) is added to a carbonization container (roller kiln) (the whole reaction is carried out in nitrogen with a gas flow rate of 10 L / h), and the carbonization temperature is raised to 350°C at a heating rate of 5°C / min and kept warm for 8 hours. According to the mass ratio of natural graphite to artificial graphite of 1:1, artificial graphite semi-finished product and modified asphalt (the ratio of artificial graphite to modified asphalt is 92.5%:7.5%) are added, and the carbonization temperature is raised to 1200°C at a heating rate of 10°C / min and kept warm for 24 hours to obtain a carbonized product. The carbonization container is a roller kiln, and the whole reaction is carried out in nitrogen with a gas flow rate of 10 L / h.

[0100] Example 4

[0101] Referring to the conditions of Example 1, only step (2) in step 3 (preparation step of composite graphite material) is changed as follows:

[0102] The mixture in (1) is added to a carbonization container (roller kiln) (the whole reaction is carried out in nitrogen with a gas flow rate of 10 L / h), and the carbonization temperature is raised to 350°C at a heating rate of 5°C / min, and the temperature is kept for 8 hours. According to the mass ratio of natural graphite to artificial graphite of 1:1, artificial graphite semi-finished product and modified asphalt (the ratio of artificial graphite to modified asphalt is 80%:20%) are added, and the carbonization temperature is raised to 1200°C at a heating rate of 10°C / min, and the temperature is kept for 24 hours to obtain a carbonized product. The carbonization container is a roller kiln, and the whole reaction is carried out in nitrogen with a gas flow rate of 10 L / h.

[0103] Example 5

[0104] Referring to the conditions of Example 1, only step (2) in step 3 (preparation step of composite graphite material) is changed as follows:

[0105] Add the mixture in (1), raise the carbonization temperature to 350°C at a heating rate of 15°C / min, and keep it warm for 8 hours. Add semi-finished artificial graphite and modified asphalt (the ratio of artificial graphite to modified asphalt is 85%:15%) according to the mass ratio of natural graphite to artificial graphite of 1:1, and raise the carbonization temperature to 1200°C at a heating rate of 15°C / min, and keep it warm for 24 hours to obtain a carbonized product. The carbonization container is a roller kiln, and the reaction is carried out in nitrogen with a gas flow rate of 10L / h throughout the process.

[0106] In the present invention, in Examples 1 to 5, the artificial graphites obtained all meet the following parameters:

[0107] The particle size D50 is 8-12μm and the specific surface area is 1-1.6m 2 / g, and the discharge capacity is 352-355mAh / g.

[0108] In the present invention, in Examples 1 to 5, the natural graphite obtained meets the following parameters:

[0109] The particle size D50 is 4-8μm and the carbon content is not less than 90wt%.

[0110] Comparative Example 1

[0111] A composite graphite material, the preparation steps of which are as follows:

[0112] (1) Mixing: Purchase natural graphite raw materials, crush them to a particle size D50 of 4-8μm, perform two-pass classification, and remove unqualified fine powder. Use a horizontal shaft ribbon mixer to mix natural graphite and resin in a ratio of 9:1 for 1 hour.

[0113] (2) High-temperature carbonization: The mixture of the two was heated to 1200°C at a heating rate of 10°C / min using a roller kiln and kept warm for 24 hours; the carbonization container was a roller kiln, and the entire reaction was carried out in nitrogen with a gas flow rate of 10 L / h.

[0114] (3) Finished product processing: The carbonized material is screened twice and demagnetized twice, and the finished product is the composite graphite material of this comparative example.

[0115] Comparative Example 2

[0116] A composite graphite material, the preparation steps of which are as follows:

[0117] (1) Grinding treatment: The petroleum coke is crushed by a jaw crusher and then pulverized by a mechanical mill to obtain powder A;

[0118] (2) Shaping: Powder A is classified once according to the particle size and then shaped twice to obtain powder B. The particle size requirement is D50: 6-8μm, and the qualified particle size ratio is >99%;

[0119] (3) Granulation: Powder B and base asphalt are mixed evenly and granulated in a reactor to obtain powder C, where the base asphalt ratio is 18%;

[0120] (4) Graphitization: Graphitize powder C at 3000°C;

[0121] (5) High-temperature carbonization: After the graphitized material and modified asphalt are evenly mixed, stir for one hour before entering the kiln, and then increase the temperature to 1200°C at a rate of 10°C / min and keep warm for 24 hours. The ratio of modified asphalt is 15%. The carbonization container is a roller kiln, and the reaction is carried out in nitrogen with a gas flow rate of 10L / h.

[0122] (6) Finished product processing: The carbonized material is subjected to two screening and two demagnetization passes, and the finished product is the composite graphite material of this comparative example.

[0123] Comparative Example 3

[0124] Referring to the conditions of Example 1, only step (2) in step 3 (preparation step of composite graphite material) is changed as follows:

[0125] The mixture in (1) was added, and the carbonization temperature was raised to 350°C at a heating rate of 15°C / min, and kept warm for 8 hours. According to the mass ratio of natural graphite to artificial graphite being 1:1, the artificial graphite semi-finished product was added, and the carbonization temperature was raised to 1200°C at a heating rate of 15°C / min, and kept warm for 24 hours to obtain the carbonized product. The carbonization container was a roller kiln, and the reaction was carried out in nitrogen with a gas flow rate of 10L / h.

[0126] Effect Example

[0127] The composite graphite negative electrode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were characterized as follows:

[0128] 1. Specific surface area test: The main test steps or test parameters are shown in Table 1:

[0129] Table 1

[0130]

[0131] 2. Particle size test: The main test steps or test parameters are shown in Table 2:

[0132] Table 2

[0133]

[0134] 3. Tap density test: The main test steps or test parameters are shown in Table 3:

[0135] Table 3

[0136]

[0137] 4. Powder pressure test: The main test steps or test parameters are shown in Table 4:

[0138] Table 4

[0139]

[0140] 5. Electrochemical performance test: The obtained negative electrode materials were assembled into batteries, and the discharge capacity and cycle number were tested. The main test steps or test parameters are shown in Table 5:

[0141] Table 5

[0142]

[0143] The test results of the materials obtained in each embodiment and comparative example are shown in Table 6:

[0144] Table 6

[0145]

[0146] From the above results, it can be seen that the composite graphite material of the embodiment of the present invention can ensure moderate basic physical and chemical parameters, and after being used in batteries, it can simultaneously ensure high discharge capacity and cycle number. Among them, in the two-step carbonization process, the first step carbonization heating rate is lower than the second step carbonization heating rate, and the effect is relatively optimal when the amount of modified asphalt is moderate.

[0147] In Comparative Example 1, the main difference compared to Example 1 is that the graphite contains only natural graphite but no artificial graphite; after using it in the battery, even if the discharge capacity is higher, the number of cycles is significantly reduced, which cannot meet the requirements of some batteries requiring high cycle performance.

[0148] In Comparative Example 2, compared with Example 1, the main difference is that the graphite contains only artificial graphite but no natural graphite. After using it in the battery, even though the cycle performance is higher, the discharge capacity is significantly reduced, and this limitation is caused by the artificial graphite itself. If other high-capacity battery materials are not mixed, this theoretical limit cannot be broken through.

[0149] In Comparative Example 3, compared with Example 1, the main difference is that when adding artificial graphite, no coating agent (modified asphalt) is added; after using it in the battery, the discharge capacity and cycle performance are significantly reduced.

[0150] It shows that in the embodiments of the present invention, the composite graphite material prepared by a specific method has excellent composite uniformity, combines the advantages of artificial graphite and natural graphite, and the obtained battery can simultaneously exhibit high discharge capacity and excellent cycle performance.

Claims

1. A method for preparing a composite graphite material, characterized in that: The preparation method of the composite graphite material comprises the following steps: S1, mixing natural graphite and a first coating agent to obtain a mixture A; S2, mixing the mixture A, artificial graphite and a second coating agent to obtain a mixture B, and carbonizing the mixture; Wherein, the first coating agent comprises resin; The second coating agent includes modified asphalt.

2. The method for preparing a composite graphite material according to claim 1, characterized in that: In step S1, the mass ratio of the natural graphite to the first coating agent is 80:20-95:5, preferably 90:10; And / or, in step S1, the mixing time is 0.5-2h, for example 1h; And / or, the mass ratio of the natural graphite in step S1 to the artificial graphite in step S2 is 1:1-1:2; And / or, in step S2, the mass ratio of the artificial graphite to the second coating agent is 80:20-90:10, preferably 85:15; And / or, in step S2, the carbonization includes a heating stage and a heat preservation stage; Wherein, the heating rate in the heating stage is preferably 10-15°C / min; Wherein, the temperature of the insulation stage is preferably 1000-1200°C; The duration of the insulation stage is preferably 22-26 hours, such as 24 hours.

3. The method for preparing the composite graphite material according to claim 1, characterized in that: In step S1, after the mixing step, a pre-carbonization step is also included; the pre-carbonization includes a heating stage and a heat preservation stage; Wherein, the heating rate in the heating stage is preferably 5-15°C / min; Wherein, the temperature of the insulation stage is preferably 300-400°C, for example 350°C; The time of the insulation stage is preferably 6-10 hours, for example 8 hours; Wherein, the pre-carbonization is preferably carried out in a roller kiln; Wherein, the pre-carbonization is preferably carried out in an inert atmosphere; Wherein, the inert atmosphere is preferably nitrogen or argon; Wherein, the gas flow rate of the inert atmosphere is more preferably 2L / h-20L / h, for example 10L / h; Preferably, the heating rate of the pre-carbonization heating stage in step S1 is lower than the heating rate of the carbonization heating stage in step S2.

4. The method for preparing a composite graphite material according to claim 1, characterized in that: In step S1, the natural graphite is spherical, and the particle size D50 of the natural graphite is preferably 4-8 μm; and / or, in step S1, the carbon content of the natural graphite is not less than 90wt%; And / or, in step S1, the purity of the resin is 65wt%-75wt%, preferably 70wt%-75wt%; And / or, in step S1, the viscosity of the resin at 25°C is 300-800cp, preferably 400-800cp; And / or, in step S1, the gelation time of the resin at 25° C. is 80-130 s, preferably 80-120 s; And / or, in step S1, the mixing is performed by a horizontal-shaft ribbon mixer.

5. The method for preparing a composite graphite material according to claim 1, characterized in that: In step S2, the carbonization is carried out in a roller kiln; And / or, in step S2, the carbonization is carried out in an inert atmosphere; Wherein, the inert atmosphere is preferably nitrogen or argon; The gas flow rate of the inert atmosphere is preferably 2 L / h-20 L / h, for example 10 L / h.

6. The method for preparing a composite graphite material according to claim 1, characterized in that: In step S2, the particle size D50 of the artificial graphite is 8-12 μm; And / or, in step S2, the specific surface area of ​​the artificial graphite is 1-1.6m 2 / g; And / or, in step S2, the discharge capacity of the artificial graphite is 352-355 mAh / g; And / or, in step S2, the method for preparing artificial graphite comprises the following steps: The steps of crushing, shaping, mixing with a binder, granulating and graphitizing the carbon raw materials; Wherein, the carbonaceous raw material is preferably petroleum coke; Wherein, the pulverizing is preferably performed by a jaw crusher; Wherein, the shaping is preferably performed by grading; Wherein, the particle size D50 of the product after shaping is preferably 6-8 μm; Wherein, the binder is preferably asphalt, such as matrix asphalt; Wherein, the amount of the adhesive is preferably 15-20% of the mass of the shaped product, for example 18%; Wherein, the graphitization temperature is preferably 2800-3000°C.

7. The method for preparing a composite graphite material according to claim 1, characterized in that: In step S2, the particle size D50 of the modified asphalt is 2-6 μm, preferably 2.5-4.5 μm; And / or, in step S2, the coking value of the modified asphalt is not higher than 30%, preferably 15-25%; And / or, in step S2, the density of the modified asphalt at 30°C is 1-1.1 g / cm 3 ; And / or, in step S2, the carbonization further includes the steps of shaping, grading, screening and demagnetization.

8. A composite graphite material, characterized in that: The composite graphite material is prepared by the method for preparing the composite graphite material according to any one of claims 1 to 7.

9. The composite graphite material according to claim 8, characterized in that The particle size D50 of the composite graphite material is 12-14 μm; And / or, the tap density of the composite graphite material is 0.9-1.4 g / cm³; And / or, the powder pressure of the composite graphite material is 1.9-2.3 g / cm³; And / or, the specific surface area of ​​the composite graphite material is 0.65-2.5m 2 / g.

10. Use of the composite graphite material according to claim 8 or 9 in the field of electrochemistry.

Citation Information

Patent Citations

  • Preparation process of composite material of artificial graphite and carbon-coated natural graphite

    CN117800335A